The fact and meaning of the resurrection : a study in emphases - Bill, Jean-Francois (Rhodes University, Faculty of Divinity, Department of Divinity, 1959)
INTRODUCTION. The fact of the Risen Christ is the focal point which gives meaning to the Christian faith as a whole. Modern thought, while not denying the Resurrection, tends to confine it to its doctrinal or credal significance. In contrast, the early Christians were conscious of the presence of the Risen Lord and consequently the Resurrection was a fact of living experience. As mere history it loses its moral significance; as mere faith it becomes vague belief in deathlessness, and undermines the reality of the Atonement. The Resurrection is both fact and faith.
Keywords: Jesus Christ -- Resurrection; Resurrection -- Biblical teaching